Localised hyperthermia in rodent models using an MRI-compatible high-intensity focused ultrasound system - Bing, Chenchen (Int J Hyperthermia, 2015)
PURPOSE: Localised hyperthermia in rodent studies is challenging due to the small target size. This study describes the development and characterisation of an MRI-compatible high-intensity focused ultrasound (HIFU) system to perform localised mild hyperthermia treatments in rodent models. MATERIAL AND METHODS: The hyperthermia platform consisted of an MRI-compatible small animal HIFU system, focused transducers with sector-vortex lenses, a custom-made receive coil, and means to maintain systemic temperatures of rodents. The system was integrated into a 3T MR imager. Control software was developed to acquire images, process temperature maps, and adjust output power using a proportional-integral-derivative feedback control algorithm. Hyperthermia exposures were performed in tissue-mimicking phantoms and in a rodent model (n = 9). During heating, an ROI was assigned in the heated region for temperature control and the target temperature was 42 °C; 30 min mild hyperthermia treatment followed by a 10-min cooling procedure was performed on each animal. RESULTS: 3D-printed sector-vortex lenses were successful at creating annular focal regions which enables customisation of the heating volume. Localised mild hyperthermia performed in rats produced a mean ROI temperature of 42.1 ± 0.3 °C. The T10 and T90 percentiles were 43.2 ± 0.4 °C and 41.0 ± 0.3 °C, respectively. For a 30-min treatment, the mean time duration between 41–45 °C was 31.1 min within the ROI. CONCLUSIONS: The MRI-compatible HIFU system was successfully adapted to perform localised mild hyperthermia treatment in rodent models. A target temperature of 42 °C was well-maintained in a rat thigh model for 30 min.